Могильник белозерской культуры у с. Хаджиллар в Юго-Восточном Буджаке - Агульников, С.М. (Материалы по археологии Северного Причерноморья, 2011)
In 1992, the Suvorovskyia expedition of the Institute of Archaeology of the Academy of Sciences of Moldavia excavated on of the barrow cemetery the Belozerka culture near the small village Hadjillar, district ?tefan-Vod?, Republic of Moldova. In 1992, there were excavated 3 steeping barrows. In the two of these three barrows (1, 3) the based graves in tumulus have a Belozerka culture attribution. The four late bronze ages graves from tumulus 2 (nr.3, 5, 18, 19) have a secondary stratigrafic position in the pit-grave culture barrow. The grave nr.3, in turn, nr.l has a difficult funeral wood construction, like a one cort. In the grave nr.3, tum.l was found the golden ring, the bimetallic knife, the vessel with a polished surface, the bones arrow and one vessel, made of wood. The archaeological complex from Hadjillar dates from the first part of the X-th century B.C. The age of Hadjillar barrow graves corresponds with the dating of Kochkovatoe and Zapovitnoye necropoles the Belozerka culture in North - Pontic steep region.